Discourses of entrepreneurial leadership: Exposing myths and exploring new approaches. (March 2017) - Dean, Hannah; Ford, Jackie
This article explores gender and entrepreneurial leadership, notably the meanings female entrepreneurs ascribe to notions of entrepreneurial leadership. Drawing from interviews with female business owners, the article questions the dominant hegemonic masculine entrepreneurial leadership model as well as that reportedly associated with women. Research findings illuminate the fluidity and variability of the entrepreneurial leadership construct. Our feminist poststructural lens and critical leadership stance adds new insight into the multiple subjectivities of entrepreneurs and surfaces contradiction and tension that shape the very sense of their entrepreneurial selves. By questioning accepted knowledge, this research offers new perspectives on the multiple realities of entrepreneurial leadership, which should be heeded by policy makers, academics and practitioners alike.